STUDI DUKUNGAN MARKETING INTELLIGENCE PADA STRATEGI PEMASARAN - Armadyah Amborowati; Armadyah Amborowati; M. Suyanto (Jurusan Teknik Informatika, 2015)
In the era of globalization of information technology needs of the organization will be very large. Evolving information technology currently used not only for the organization of daily transactions but also to support a competitive advantage, especially in making marketing strategies. Information technology to support marketing strategies one of them is business intelligence. This paper analyzes business intelligence support, especially in the field of marketing intelligence on marketing strategy with the method used is the study of literature. And the result is that support marketing intelligence on the marketing strategy of the technology is to market segmentataion / consumer and one of them with data mining technology.